Inflation, Markups and Monetary Policy - Magnus Jonsson; Stefan Palmqvist (Sveriges Riksbank, 2003)
The correlation between persistent changes in the markup in one sector of an economy and the inflation rate is quantified in a 2-sector dynamic general equilibrium model. How this relationship is affected by monetary policy is also studied. We find that the correlation is in general positive under an exogenous money growth rule as well as under an inflation targeting rule. That is, a decrease of the markup leads to a decrease in the CPI-inflation rate. However, if inflation is measured by an optimal price index that also includes the wage rate the correlation is slightly negative. That is, a decrease in the markup leads to higher inflation rates. This is due to higher wage rates. The correlation is sensitive to whether the policy rule includes an output term. If monetary policy accommodates output strongly the correlation is negative. A decrease in the markup leads to higher inflation rates, as measured by both the CPI and the optimal price index.
Keywords: D43; E31; E52; 330; Price indices; monopolistic competition; monetary policy rules